PALAEOGEOTHERMS - IMPLICATIONS OF DISEQUILIBRIUM IN GARNET LHERZOLITE XENOLITHS - Fraser, D; Lawless, P (1978)
MEASURES of the Earth's thermal structure and evolution are important for understanding the driving forces of many geological processes. Estimates of the present variation of temperature with depth in the Earth can be made from surface heat-flow values together with assumptions concerning the composition, thermal conductivity and heat production of the crust and mantle1. More direct estimates have been made by calculating equilibrium temperatures and pressures of material brought to the Earth's surface as nodules in kimberlite pipes2,3 and volcanoes4. Results from the latter studies have been used to describe the equilibrium distribution of temperature and pressure within the Earth3 at times from the Precambrian 5-8 to the late Mesozoic9. Although there has been much discussion of the exact shape3,10-12 and significance13,14 of the calculated geothermal gradients, it has generally been assumed that the calculated values of temperature and pressure are estimates of the true equilibrium conditions of the assemblage. Here the basic assumption of chemical equilibrium is examined critically and it is shown that the calculated geotherms may be at least partly spurious. The distribution in calculated temperatures and pressures can be explained by the inherent temperature dependence of the geobarometer and the failure of the assemblages to equilibrate with respect to all components. © 1978 Nature Publishing Group.